Exploring Students’ Perception on Using English Movie for Listening Skills Improvement - Siti Safura (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study was aimed to look into students’ perception of using English movie in increasing listening skills. This study was quantitative research with using survey design. The survey was a way to collect the data how students perceived the use of English movie in listening classroom. Ten questionnaires were distributed to 28 students of second grade level at Lab School Unsyiah. The obtained data was analyzed descriptively based on students’ frequency. The result of this study showed majority of students felt positive with the use of English movie in developing the listening ability. The use of English movie in listening class assist students to learn and understand the speaker are saying. Therefore, the use of English movie was the preference media in learning English particularly to improve students’ listening skills.